2019
DOI: 10.3892/ol.2019.10974
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression levels of ELOVL6 indicate poor prognosis in hepatocellular carcinoma

Abstract: The present study aimed to investigate the expression of elongation of very long-chain fatty acids family member 6 (ELOVL6) in hepatocellular carcinoma (HCC) tissues, and to determine its role in the development of HCC. A total of 377 HCC specimens were collected for tissue microarray and immunohistochemistry analyses. The ELOVL6 IHC score for HCC tissues was 0.97±0.71, which was significantly lower than that of the matched adjacent normal tissues (1.32±0.68; P<0.001). Patients with low levels of ELOVL6 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…ELOVL5 has been shown to be markedly upregulated in prostate carcinoma cells and its inhibition has been detrimental to prostate cancer cell survival [52]. The status of ELOVL6 in cancer is less clear, as both increased and decreased expression have been reported to correlate negatively with cancer progression and patient survival in breast or liver cancer [53][54][55]. The downregulation of ELOVL6 observed in our study corresponded with the lack of upregulation of stearic acid, which is a major product of this enzyme [56,57].…”
Section: Discussionsupporting
confidence: 48%
“…ELOVL5 has been shown to be markedly upregulated in prostate carcinoma cells and its inhibition has been detrimental to prostate cancer cell survival [52]. The status of ELOVL6 in cancer is less clear, as both increased and decreased expression have been reported to correlate negatively with cancer progression and patient survival in breast or liver cancer [53][54][55]. The downregulation of ELOVL6 observed in our study corresponded with the lack of upregulation of stearic acid, which is a major product of this enzyme [56,57].…”
Section: Discussionsupporting
confidence: 48%
“…Finally, the pressing need for optimized energetic pathways facing nutrient shortage drives enhanced glucose uptake ( SLC2A3/GLUT3) 47,48 and lipid catabolism ( RORA, ANGPTL4) 49,50 . The later includes the upregulation of carnitine transporters ( SLC22A15) 51 , while counteracting lipogenesis ( ELOVL6) through rate limiting enzymes downregulation 52 and promotion of autophagic events ( DDIT4, HK2, PFKFB3, DEPP1 ) 5356 . Significantly differentially expressed genes were then clustered by gene ontology and the enrichment of gene ontology terms was tested using Fisher’s exact test ( Figure 2D ).…”
Section: Resultsmentioning
confidence: 99%
“…Knockdown of ELOVL6 expression inhibited hepatocellular carcinoma cell proliferation in vitro and in vivo (33). Meanwhile, a positive correlation was observed between high ELOVL6 expression and the survival of patients with hepatocellular carcinoma (37). Our IHC results showed that the expression of ELOVL6 was low in the tissues of patients with COAD.…”
Section: Discussionmentioning
confidence: 58%